Integrating The Marketing-Finance Interface In Marketing and IMC Strategy Formulation: A Case Study of Dove Shampoo - Nugraha, Galuh Satya; Kurniawan, Gogi; Hafidulloh; Haryanti, Endri (UMSurabaya Publishing, 2025)
The Indonesian FMCG industry, especially in the hair care segment, faces intense competition as consumers increasingly prioritize emotional and social values in purchasing decisions. This study examines how the marketing–finance interface supports integrated marketing communication (IMC) strategies to strengthen brand competitiveness. Using a qualitative case study of PT Unilever Indonesia Tbk and its Dove brand, data were collected through in-depth interviews with key managers and analysis of internal documents. Thematic analysis revealed that functional integration—through joint decision-making forums, cross-departmental performance indicators, and cross-training programs—enhances IMC effectiveness and enables data-driven strategic decisions. The findings highlight the strategic importance of cross-functional collaboration in developing communication strategies that are both emotionally resonant and financially accountable. This research contributes to the marketing–finance interface literature in emerging markets and provides practical insights for FMCG firms seeking to align marketing creativity with financial discipline. Keywords: Marketing–Finance Interface, Integrated Marketing Communication, Consumer Behavior, FMCG Strategy